TNF-α–Induced miR-21-3p Promotes Intestinal Barrier Dysfunction by Inhibiting MTDH Expression - Jiang, Zhifeng; Yang, Feiyu; Qie, Jingbo; Jin, Chaoyuan; Zhang, Feng; Shen, Jie; Zhang, Lin (Frontiers in Pharmacology, 2021)
Intestinal barrier dysfunction is characterized by increased intestinal permeability to lumen endotoxin, showing remarkable predisposition to immune enteropathy and colorectal cancer (CRC). Tumor necrosis factor (TNF)-α is associated with this pathological process, while the mechanism remains unknown. In this study, different doses of TNF-α were used for Caco-2 cells treatment. We discovered that miR-21-3p expression was obviously increased by TNF-α in a dose-dependent manner. Further study demonstrated that TNF-α could upregulate miR-21-3p expression through NF-κB signaling pathway. Then, TargetScan and miRWalk miRNA-mRNA interaction prediction online tools were introduced and Metadherin (MTDH) was screened out as a potential target of miR-21-3p. We subsequently found that miR-21-3p could directly target the 3’-untranslated region (UTR) of MTDH mRNA and inhibit its expression. Furthermore, it was demonstrated that miR-21-3p could regulate Wnt signaling pathway by targeting MTDH mRNA, suggesting the effect of miR-21-3p/MTDH/Wnt axis on intestinal barrier dysfunction. Our findings provide a novel potential biomarker and therapeutic target for intestinal barrier dysfunction and related diseases.